Development of interactive e-worksheets to improve counting skills of children aged 5-6 years - Salsabila Ramadhan; ⁠Setiyo Utoyo; Dadan Suryana; Yaswinda Yaswinda (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
This research aims to develop a valid, practical, and effective interactive e-worksheet utilizing Canva, and Liveworksheets platforms based on Jerome Bruner’s cognitive development theory (enactive, iconic, symbolic) to improve the counting abilities of children aged 5-6 years. Using the ADDIE (Analyze, Design, Develop, Implement, Evaluate) research and development (R&D) model, this study was conducted at TK Pautan Hati Sungai Tambang during the 2025/2026 academic year. The subjects consisted of 5 children for the pilot test and 20 children for the field test. Data were collected using expert validation sheets, teacher practicality questionnaires, and children's counting performance tests (pretest and posttest). Formative evaluation from media, material, and evaluation experts showed a cumulative validation score of 94.08% (Highly Valid). The teacher's practicality response reached 97.00% (Highly Practical). Furthermore, quantitative analysis demonstrated a significant increase in children's average counting scores from 53.25 (pretest) to 89.50 (posttest). The efficiency was confirmed by a Normalized Gain (N-Gain) score of 0.776 (High Effectiveness) and a Wilcoxon Signed Rank Test significance value of 0.000 (p<0.05). In conclusion, the developed interactive e-worksheet is highly feasible, practical, and effective to be implemented in early childhood numerative learning.